Subjective well-being dan perilaku kecanduan online games pada mahasiswa - Claudia Dian Ratna Sari; Christiana Hari Soetjiningsih (JURNAL SPIRITS, 2020)
This study aims to examine the relationship between Subjective Well-being and Online Games Addiction in college student. Participants were 63 Psychology Faculty students from SWCU, who played online games at least 3 hours a day, which were obtained by using a purposive sampling technique. The data collection method uses Subjective Well-being scale consisting of Manual for Multidimensional Student Life Satisfaction (MSLSS) to measure life satisfaction and Scale of Positive and Negative Experience (SPANE) to measure affect, and the Online Games Addiction Scale to measure online games addiction. Data analysis using Pearson’s product moment correlation technique showed r = -0.057 and significance value of 0.330 (p>0.05) which meant there was no relationship between Subjective Well-being and Online Games Addiction for college students.Keywords: subjective well-being; online games addiction, students